Investigating the biochar effects on C‐mineralization and sequestration of carbon in soil compared with conventional amendments using the stable isotope (δ13C) approach. Issue 6 (29th November 2016) - Yousaf, Balal; Liu, Guijian; Wang, Ruwei; Abbas, Qumber; Imtiaz, Muhammad; Liu, Ruijia
Abstract: Biomass‐derived black carbon (biochar) is considered to be an effective tool to mitigate global warming by long‐term C‐sequestration in soil and to influence C‐mineralization via priming effects. However, the underlying mechanism of biochar (BC) priming relative to conventional biowaste (BW) amendments remains uncertain. Here, we used a stable carbon isotope ( δ 13 C) approach to estimate the possible biochar effects on native soil C‐mineralization compared with various BW additions and potential carbon sequestration. The results show that immediately after application, BC suppresses and then increases C‐mineralization, causing a loss of 0.14–7.17 mg‐CO2 –C g −1 ‐C compared to the control (0.24–1.86 mg‐CO2 –C g −1 ‐C) over 1–120 days. Negative priming was observed for BC compared to various BW amendments (−10.22 to −23.56 mg‐CO2 –C g −1 ‐soil‐C); however, it was trivially positive relative to that of the control (8.64 mg‐CO2 –C g −1 ‐soil‐C). Furthermore, according to the residual carbon and δ 13 C signature of postexperimental soil carbon, BC‐C significantly increased ( P < 0.05) the soil carbon stock by carbon sequestration in soil compared with various biowaste amendments. The results of cumulative CO2 –C emissions, relative priming effects, and carbon storage indicate that BC reduces C‐mineralization, resulting in greater C‐sequestration compared with other BW amendments, and the magnitude of this effect initially increases and then decreases and stabilizes over time, possibly due to the presence of recalcitrant‐C (4.92 mg‐C g −1 ‐soil) in BC, the reduced microbial activity, and the sorption of labile organic carbon (OC) onto BC particles. Abstract : Biochar reduces C‐mineralization, resulting in greater C‐sequestration compared with other BW amendments, and the magnitude of this effect initially increases and then decreases and stabilizes over time, possibly due to the presence of recalcitrant‐C in biochar.